2021
DOI: 10.1038/s41598-021-98101-w
|View full text |Cite
|
Sign up to set email alerts
|

Histone-like nucleoid-structuring protein (H-NS) regulatory role in antibiotic resistance in Acinetobacter baumannii

Abstract: In the multidrug resistant (MDR) pathogen Acinetobacter baumannii the global repressor H-NS was shown to modulate the expression of genes involved in pathogenesis and stress response. In addition, H-NS inactivation results in an increased resistance to colistin, and in a hypermotile phenotype an altered stress response. To further contribute to the knowledge of this key transcriptional regulator in A. baumannii behavior, we studied the role of H-NS in antimicrobial resistance. Using two well characterized A. b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Among the three mycosyl transferase genes of Mycobacterium tuberculosis, only the mutation of fbpA was considered to weaken the growth of this species in macrophages. Fade14 gene was also predicted in this study, FadE14 is part of an iron and IdeR repressible operon which produces a polycistronic message encoding FadE14, FadD33 and an acyl carrier protein (acp), in Mycobacterium smegmatis, FadE14 were necessary for wild-type mycobactin production (Rodgers et al, 2021). The ability to metabolize fatty acids seems to be crucial to the toxicity of Streptococcus equi.…”
Section: Discussionsupporting
confidence: 61%
“…Among the three mycosyl transferase genes of Mycobacterium tuberculosis, only the mutation of fbpA was considered to weaken the growth of this species in macrophages. Fade14 gene was also predicted in this study, FadE14 is part of an iron and IdeR repressible operon which produces a polycistronic message encoding FadE14, FadD33 and an acyl carrier protein (acp), in Mycobacterium smegmatis, FadE14 were necessary for wild-type mycobactin production (Rodgers et al, 2021). The ability to metabolize fatty acids seems to be crucial to the toxicity of Streptococcus equi.…”
Section: Discussionsupporting
confidence: 61%
“…Transcriptome analysis of A. baumannii AB5075 and AB5075 Δhns cultured in LB broth revealed a differential expression profile of 183 genes 22 . When A. baumannii AB5075 was cultured in LB broth with or without HSA there were 30 genes differentially expressed (Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic modifications in quorum sensing were assessed determining levels of acyl-homoserine lactone (AHL) using the Agrobacterium tumefaciens -based solid plate assays 28 , 29 . Rodgers et al demonstrated that the supernatants from A. baumannii AB5075 or AB5075 Δhns produced similar intensity of color, likely caused by an increase in both AHL synthesis (quorum sensing) and lactonase activity (quorum quenching) in AB5075 Δhns strain 22 . To study the effect of HSA on AHL secretion into the surrounding medium, A. baumannii AB5075, AB5075 Δhns, and the strains complemented with pMBLe- hns were cultured in different conditions before assessing the AHL concentration in the growth medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations